MILITARY CULTURE AND DEFENSE MANAGEMENT IN AZERBAIJAN: CONTEMPORARY TRANSFORMATIONS - Naiba SHAMSHIYEVA (Journal of Defense Resources Management)
The article is dedicated to studying military culture, which is of special relevance in military administration in modern times and acts as an important means of socialization between the army and society. In the article, based on various scientific sources, the author tried to reveal military culture's characteristic features and content and exhibited a specific scientific approach to its structural elements and forms. The analysis of new concepts and categories included in the value standards of military culture in the process of building an army in connection with the emergence of a new political way of thinking in Azerbaijani society formed a special subject of research in the article. The article also put forward specific considerations regarding the possibilities of applying military culture in the training of qualified officer personnel in the Azerbaijani army, as well as development prospects. As a result, in the article, taking advantage of the historical experience, the involvement of the achievements of all fields of culture in the field of military activity as a whole was evaluated as one of the important requirements facing the army, and the synthesis of all the achievements of the military culture with the reforms carried out in the military field was expressed as a guarantee of the success, success and reliable future of the army. To strengthen the value standards of military culture in the future in the process of building an army, their continuous promotion among personnel is reflected in the article as the main proposal.